2001
DOI: 10.1007/bf02317799
|View full text |Cite
|
Sign up to set email alerts
|

The effects of autonomic dysfunction and endurance training on cardiovascular control

Abstract: The effects of autonomic dysfunction and regular activity on the cardiovascular system were investigated. The 48 participants included 12 subjects with tetraplegia, 12 subjects with paraplegia, 12 sedentary subjects, and 12 endurance-trained able-bodied controls. Central and peripheral autonomic data were obtained at rest to estimate efferent cardiac vagal output and sympathetic vasomotor control, and plasma norepinephrine concentration was determined as a marker of peripheral sympathetic activity. Cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…hemodynamics were similar between the groups at supine rest and during acute HDT and HUT, as previously reported (12,18,20,38). CO during passive tilting is maintained by increases in heart rate, which are compensatory to losses in central filling pressure, venous return, and reduced stroke volume (13).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…hemodynamics were similar between the groups at supine rest and during acute HDT and HUT, as previously reported (12,18,20,38). CO during passive tilting is maintained by increases in heart rate, which are compensatory to losses in central filling pressure, venous return, and reduced stroke volume (13).…”
Section: Discussionsupporting
confidence: 84%
“…These concomitant problems facing individuals with paraplegia suggest that they would be highly susceptible to orthostatic intolerance. Despite significant reductions in muscle mass and sympathetic activity of the lower extremity, resting and orthostatic cardiac hemodynamics, i.e., CO, stroke volume, and heart rate, have been reported as similar in persons with paraplegia and nondisabled controls (11,12,18,20,38). It is unclear how central hemodynamics are maintained during gravitational stress in persons with lower ex-tremity denervation and skeletal muscle atrophy.…”
mentioning
confidence: 99%
“…modulator of resting vagosympathetic cardiac control. 43,44 Athletes with SCI have also demonstrated some ability to improve CV modulation through exercise, 44,45 although not to the extent of athletes with intact ANS. 46,47 To address the question as to how ANS dysfunction relates to Paralympic classification, it is important to look specifically at the response to exercise in SCI athletes.…”
Section: Effect Of Sci On Elite Athletes' Exercise Performancementioning
confidence: 99%
“…Several studies report orthostatic hypotension in people with tetraplegia (Houtman et al 2000;Illman et al 2000), while it is not clear whether regular physical activity improves autonomic regulation during orthostatic challenges. A lower resting heart rate and higher vagal tone have been reported in endurance-trained able-bodied athletes (Wecht et al 2001). Amano et al (2001) reported that obese individuals, who manifested lower SNS activity against physiological perturbations, improved both the sympathetic and parasympathetic nervous activity after 12 weeks of endurance exercise training.…”
Section: Introductionmentioning
confidence: 97%